2021
DOI: 10.1186/s12985-021-01651-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of Artemisia extracts against SARS-CoV-2

Abstract: Background Traditional medicines based on herbal extracts have been proposed as affordable treatments for patients suffering from coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Teas and drinks containing extracts of Artemisia annua and Artemisia afra have been widely used in Africa in efforts to prevent SARS-CoV-2 infection and fight COVID-19. Methods The plant extracts and Covid-Organics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 24 publications
1
46
3
Order By: Relevance
“…The lowest ART content (BUR) yielded the greatest potency (the lower the IC 50 , the more potent the drug/extract), providing evidence that ART is not the only active antiviral agent in these extracts. Nie et al (2021) further validated that ART was not the only anti-SARS-CoV-2 compound in the extracts by showing that aqueous extracts of the PAR cultivar of Artemisia afra , an Artemisia species lacking ART, had an IC 50 of 4.1 mg/mL, within the range of 3.1–13.0 mg dried extract/mL of the A. annua cultivars studied therein. As already reported for extracts used in this study, no cytotoxicity was observed at a dry weight of ≤50 μg in the extract of any cultivar ( Nair et al, 2021 ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The lowest ART content (BUR) yielded the greatest potency (the lower the IC 50 , the more potent the drug/extract), providing evidence that ART is not the only active antiviral agent in these extracts. Nie et al (2021) further validated that ART was not the only anti-SARS-CoV-2 compound in the extracts by showing that aqueous extracts of the PAR cultivar of Artemisia afra , an Artemisia species lacking ART, had an IC 50 of 4.1 mg/mL, within the range of 3.1–13.0 mg dried extract/mL of the A. annua cultivars studied therein. As already reported for extracts used in this study, no cytotoxicity was observed at a dry weight of ≤50 μg in the extract of any cultivar ( Nair et al, 2021 ).…”
Section: Resultsmentioning
confidence: 74%
“…Others also observed that compared to A. annua L., A. afra Jacq. ex Willd., a related perennial species lacking ART, was equally effective against SARS-CoV-2 with IC 50 values of 0.9–3.4 and 0.65 mg/mL extract, respectively ( Nie et al, 2021 ). Although those results indicated that both A. annua and A. afra have potent anti-SARS-CoV-2 activity in vitro and that the effect was not ART-dependent, it was unclear whether A. annua is effective against emerging variants.…”
Section: Introductionmentioning
confidence: 99%
“…However, effective antivirals are still needed for patients who are not vaccinated yet or when the vaccines fail to work efficiently. Treatment of COVID-19, unfortunately, remains largely supportive [27]. Many researchers have conducted studies on the antiviral activity of the currently utilized drugs for different diseases which are called drug repurposing.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Recently, it has also been shown that plant extracts from Artemisia annua, which contain artemisinin, exhibit antiviral activity against SARS-CoV-2 in vitro. [9] These findings back the hypothesis, that African countries have been hit later and weaker by the pandemic than expected, due to widespread use of artemisinin based traditional antimalarial medicine or artemisinin-based combination therapy (ACT). [10] The anti-SARS-CoV-2 potential of artemisinins (Figure 1A) was also determined in a pharmacokinetic model in vitro.…”
Section: Introductionmentioning
confidence: 90%